Hard polycrystalline eutectic composite prepared by spark plasma sintering - Grasso, Salvatore (2013)
A polycrystalline eutectic B4C–TiB2 composite was prepared by spark plasma sintering. The starting eutectic powder was obtained by mechanical grinding of the directionally solidified eutectic B4C–TiB2 alloy. The microstructure of the polycrystalline composite exhibited randomly oriented eutectic grains with an average size of about 50–100 μm. Eutectic grains consisted of boron carbide matrix reinforced by titanium diboride inclusions. The secondary eutectic structure in the grain boundary is formed at sintering temperature higher than 1700 °C. XRD analysis revealed that the eutectic B4C–TiB2 composite consist mainly of B4C and TiB2 phases. The measured Vickers hardness was in the range of 32.35–54.18 GPa and the average fracture toughness of the samples was as high as 4.81 MPa m1/2. The bending strengths of the composite evaluated at room temperature and at 1600 °C were 230 and 190 MPa, respectively.